Spatial equilibrium model for AGRODEP - Bouët, Antoine; Metivier, Jeanne (International Food Policy Research Institute, 2017)
This technical note aims to introduce a spatial equilibrium model (SEM) to AGRODEP members. Specifically, by using simplified data, a pedagogic tool is developed to explain the design of a spatial equilibrium model. The potential uses of the model, regarding trade policy analysis as well as transportation costs variation analysis, are exemplified by means of two distinct scenarios. Moreover, this technical note provides a specific focus on the process of calibrating the initial data of the model: supply and demand, prices, trade, and transportation costs. The spatial equilibrium model is a multi-region partial equilibrium model which links producers and consumers from different locations. It allows economists to examine the global economic and trade consequences of diverse trade policies by determining their effects on market, trade and welfare variables. As an example, it evaluates the impact of such policies on supply and demand, producer and consumer prices, volume and direction of trade, consumer and producer surpluses, as well as on world welfare.